Analysing diversion processes in German Secondary Education : school-track effects on educational aspirations - Bittmann, Felix [Verfasser]; Schindler, Steffen [Verfasser] (My University, 2021)
Educational aspirations can be regarded as a predictor of final educational attainment, rendering this construct highly relevant for analysing the development of educational inequalities in panel data settings. In the context of the German tracked secondary school system, we analysed school-track effects on the development of educational aspuations. Using data from five consecutive waves of the National Educational Panel Study (NEPS), we selected a sample of high-performing students with initially high aspirations. Our results indicate that pupils in the nonacademic track or with a low social origin tend to lower their aspirations significantly more often than pupils in the academic track or pupils with a high social origin. With mediation analyses, we demonstrate that these differences can be attributed to learning environments at the school level. We also show that the down ward adjustment of aspirations in the nonacademic track is less pronounced for students from highly educated families than for students from low-education family backgrounds. ( Author's abstract ; BIBB-Doku)

"Da Bildungsaspirationen als Prädiktoren der final erreichten Bildungsabschlüsse betrachtet werden können, erscheint dieses Konstrukt von größter Relevanz bei der Analyse der Entstehung von Bildungsungleichheiten im Längsschnitt. Im Kontext der deutschen Sekundarstufe analysieren wir den Effekt von Schularten auf Bildungsaspirationen. Dazu nutzen wir fünf konsekutive Befragungswellen des Nationalen Bildungspanels (NEPS) und untersuchen eine Subpopulation aus leistungsfähigen Schülerinnen und Schülern mit anfangs hohen Aspirationen. Die Ergebnisse belegen, dass insbesondere Schüler in nichtgymnasialen Schulformen oder solche aus benachteiligter sozialer Herkunft dazu neigen, hohe Bildungsaspirationen über die Zeit hinweg zu verlieren. Durch Mediationsanalysen zeigen wir, dass diese Effekte zum Teil durch die unterschiedlichen Lernumwelten der Schularten vermittelt werden. Darüber hinaus lässt sich nachweisen, dass sich die negativen Effekte nichtgymnasialer Schulformen vor allem auf sozial benachteiligte Kinder auswirken. Schüler privilegierter sozialer Herkunft sind weniger stark betroffen." (Autorenreferat ; BIBB-Doku)
Keywords: G 1.3.2 Bildungsverhalten und -verläufe; P 1.7 Benachteiligte; 370; Bildungsaspirationen; soziale Herkunft; Schulform; Hauptschule; Realschule; Benachteiligter Jugendlicher; Nationales Bildungspanel